(untitled) (Research, Society and Development, 2021)
Introduction: Self-injurious behaviour is defined as an act directed at oneself that results in tissue damage. Oral structures can be traumatized by this type of behaviour and its incidence is increasing among children. Objective: To present the factors associated with oral self-mutilation in children and adolescents, in order to assist the clinician in the differential diagnosis of oral lesions. Methodology: An integrative literature review was carried out based on a search in the Medline databases (PubMed), between 2010 and 2020. 27 articles were selected, being 5 case-control, 1 cross-sectional and 21 case reports. Results: The evaluated studies were developed in several countries, in hospitals, outpatient clinics, institutes, universities, schools and orphanages. In observational studies, the samples varied between 30 and 303 participants. Oral self-mutilation was related to social, hereditary, neurological and psychiatric factors. It was also observed the involvement of individuals without comorbidities in cases of oral self-mutilation. In these studies, there were more children than adolescents involved in oral self-mutilation. Conclusion: Hereditary, neurological, psychiatric and social factors are pointed out as factors associated with oral self-mutilation in children and adolescents. However, the literature is still scarce in standardizing the protocol for diagnosing oral self-mutilation, so further studies are needed to determine what factors may be relevant to these cases when involving children and adolescents.